SAFETY OF CONSUMER GOODS AS THE MAIN PROBLEM OF MODERN COMMODITY SCIENCE - VASIUTA, VIKTORIIA; ZIELOV, ROSTYSLAV; OMELIANENKO, KONSTIANTYN (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The problem of the safety of consumer goods and the way they are stored is relevant in the modern world. Particular attention is paid to the issue of packaging, namely the choice of this type of packaging, which will not harm the health of consumers. the issue of reducing the negative impact on the environment is also important. Currently, one of the main directions in the development of commodity science is the problem of the safety of consumer goods. With the development of scientific and technological progress and the globalization of production, the number and scale of goods produced are constantly increasing. In these conditions, control over the complete quality control of the product itself is lost. Therefore, the issue of product safety is becoming increasingly important. The main task of product quality control is to provide consumers with products that will not harm their physical and psychological health. Harmful substances pose a danger not only to humans, but also to the environment. The packaging of goods also has a negative impact on nature. It is necessary to ensure the ability to decompose in nature or to introduce systems for the recycling of such materials (recycling). Today, the pollution of the environment in Ukraine with harmful substances is quite high, but modern science is able to minimize this problem as much as possible. The article discusses the existing types of dangers from low-quality food products, the negative impact of some types of packaging on human health. The main possible ways of processing the packaging of goods after their consumption are considered. The authors believe that in Ukraine it is necessary to strengthen the quality control of goods, introduce and stimulate the development of recycling and disposal of packaging to ensure the preservation of the health of citizens and reduce the impact on the environment of negative factors of human existence. The authors noted that in order to minimize the negative impact on the environment, manufacturers need to use safe materials for packaging. Consumers are encouraged to support those manufacturers who produce quality products and promote innovative recycling systems. The production of ecological, safe goods, their safe processing and disposal, ecological packaging do not lose their relevance and have become one of the main directions of development of modern commodity science.
Keywords: commodity science; safety; human health; product safety; product quality; packaging